How Can Digital Entrepreneurship Address Social Issues? The Case of EkoHarita in Fighting Ecological Disruption - Ozsoy, Zeynep; Oba, Beyza (Routledge, 2022)
[Abstract Not Available]
Keywords: Sharing Economy; Models